Effectiveness of Role-Playing on Arabic Language Skills in Higher Education: A Systematic Literature Review - Machmud Yunus; Imam Machali; Rohmatun Lukluk Isnaini; Muhajir (Asalibuna, 2026)
Arabic language learning in non-Arabic-speaking contexts often faces challenges related to limited communicative practice, low engagement, and insufficient interactive opportunities. Addressing these issues through communicative, student-centered education, this systematic literature review aimed to evaluate the effectiveness of role-playing in improving Arabic language proficiency in higher education. Following the PRISMA 2020 guidelines, a comprehensive search was conducted across four electronic databases (ERIC, Google Scholar, Springer Nature Link, and Wiley Online Library) for empirical quantitative studies published between 2015 and 2025. The methodological quality of eligible studies was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. Six higher education studies met the inclusion criteria. A comparative synthesis showed that quasi-experimental studies consistently reported improvements in objective language outcomes, particularly speaking fluency, dialogue competence, and vocabulary acquisition. Conversely, cross-sectional survey studies primarily highlighted gains in learner motivation, self-confidence, engagement, and communicative competence. Notably, implementations featuring authentic scenarios, collaborative activities, and active instructor facilitation yielded broader linguistic and affective benefits. Despite variations in study design and duration, the methodological quality ranged from moderate to high. Overall, role-playing is an effective, low-cost, and adaptable pedagogical strategy. These findings support integrating structured role-playing activities into Arabic language curricula while emphasizing thoughtful instructional design to maximize learning outcomes.   Abstrak Pembelajaran bahasa Arab di konteks non-penutur asli sering kali menghadapi tantangan terkait keterbatasan praktik komunikatif, rendahnya keterlibatan pembelajar, dan kurangnya kesempatan belajar interaktif. Menjawab tantangan tersebut melalui pendekatan pendidikan yang komunikatif dan berpusat pada siswa, tinjauan literatur sistematis ini bertujuan untuk mengevaluasi efektivitas teknik role-playing dalam meningkatkan kemahiran bahasa Arab di perguruan tinggi. Mengikuti panduan PRISMA 2020, pencarian komprehensif dilakukan di empat basis data elektronik (ERIC, Google Scholar, Springer Nature Link, dan Wiley Online Library) untuk penelitian kuantitatif empiris yang terbit antara tahun 2015 dan 2025. Kualitas metodologis dari studi yang memenuhi syarat dinilai menggunakan Joanna Briggs Institute (JBI) Critical Appraisal Tools. Enam studi di tingkat perguruan tinggi memenuhi kriteria inklusi. Sintesis komparatif menunjukkan bahwa studi kuasi-eksperimental secara konsisten melaporkan peningkatan pada hasil bahasa yang objektif, terutama kelancaran berbicara, kompetensi berdialog, dan penguasaan kosakata. Sebaliknya, studi survei potong-lintang terutama menyoroti peningkatan pada motivasi, kepercayaan diri, keterlibatan, dan kompetensi komunikatif pembelajar. Penerapan yang menggunakan skenario otentik, kegiatan pembelajaran kolaboratif, dan fasilitasi aktif dari pengajar terbukti memberikan manfaat linguistik dan afektif yang lebih luas. Terlepas dari variasi desain dan durasi penelitian, kualitas metodologis secara umum tergolong sedang hingga tinggi. Secara keseluruhan, role-playing merupakan strategi pedagogis yang efektif, berbiaya rendah, dan adaptif. Temuan ini mendukung pengintegrasian aktivitas role-playing terstruktur ke dalam kurikulum bahasa Arab dengan menekankan pentingnya rancangan pembelajaran untuk memaksimalkan hasil belajar.